TEACHERS’ TPACK DEVELOPMENT IN ENGLISH LANGUAGE TEACHING: A SYSTEMATIC REVIEW - Ilahude, Fidya Felinda; Inawati, Iin; Pratolo, Bambang Widi (Premise: Journal of English Education and Applied Linguistics, 2023)
This study aims to analyze the characteristics and trends in 25 research articles published from 2018 to 2022 on English teachers’ TPACK development issues and to find themes that emerge from the articles analyzed. The research articles reviewed in this study were based on the following criteria: (1) peer-reviewed studies, (2) TPACK-related studies in the ELT context, and (3) published within the last five years. These articles were searched electronically using search engine databases such as SpringerLink, Proquest, and ERIC indexed by SCOPUS. The research results showed that the research design employed by the articles reviewed were case study (55%), descriptive studies (15%), quasi-experiments (5%), collaborative action research (10%), mixed methods (5%), and exploratory survey research (10%). It was found also that there were five common themes of findings, including (1) comparisons of pre-service, in-service and teacher formation programs on TPACK in ELT, (2) reflections on overcoming the complexities of TPACK for EFL Teachers, (3) video projects in TPACK, (4) implementation of the TPACK Framework by English teachers due to the COVID-19 Pandemic, and (5) application of the TPACK framework by developing Indonesian EFL teachers' TPACK online. Based on the literature review analysis, this research's pedagogical implications are expected to increase technology readiness and the use of English language instructors in various teaching and learning contexts in the classroom.